PERANCANGAN KEMASAN PLASTIK ISI ULANG PADA IKM KOTA CILEGON UNTUK MENINGKATKAN NILAI TAMBAH MASYARAKAT - Gunawan, Akbar; Febianti, Evi; Ekawati, Ratna (Universitas Sultan Ageng Tirtayasa, 2018)
One of the Ministry of Industry and Trade assistants in the city of Cilegon produces types of liquid soap whose products are named Her Clean. Products produced include dishwashing liquid soap, floor cleaning liquid, glass cleaner, clothes lubricant, clothes perfume, handwashing liquid soap, vehicle washing soap liquid, vehicle tire polish and so on. During this time the IKM packaged liquid soap products using plastic bottles of various sizes. After conducting a survey by asking consumers around Cilegon, they want to make refill packs made from plastic which can also be used daily with added value as a secondary product. So that this study aims to design plastic refill packs of liquid soap products in the city of Cilegon Ikm to increase community added value. The results obtained from the community service research were obtained by refill plastic packaging in the form of 450ml size pounch which was representative in accordance with the added value and consumer desires such as standing pounch, thick, transparent, spoutpack, and complete labeling containing how to use, barcode, net, production